2018
DOI: 10.1002/jcla.22447
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to lymphocyte ratio in acute aortic dissection

Abstract: Indices derived from full cell blood count may provide diagnostic information in patients with AAD; whether these indices may contribute to prognosis assessment should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…When our findings were examined, it was found that pseudoaneurysms were compatible within the literature in terms of the risk of development by hypertension, chronic kidney disease and the inappropriate area of intervention (1,2,6). When we examine the literature (11)(12)(13)(14), we see that there are studies on new markers aimed at supporting diagnosis in anticipating the follow-up, treatment and complications of peripheral vascular, aorta and cardiac diseases. In particular, the number and ratio of various cell elements in CBC are used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When our findings were examined, it was found that pseudoaneurysms were compatible within the literature in terms of the risk of development by hypertension, chronic kidney disease and the inappropriate area of intervention (1,2,6). When we examine the literature (11)(12)(13)(14), we see that there are studies on new markers aimed at supporting diagnosis in anticipating the follow-up, treatment and complications of peripheral vascular, aorta and cardiac diseases. In particular, the number and ratio of various cell elements in CBC are used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that inflammatory response occurs in cases with Deep vein thrombosis (DVT) developed (12,14). In these patients, we have come across publications examining the relationship between inflammatory parameters such as C-reactive protein (CRP) and interleukin and platelet distribution range (PDW), mean platelet volume (MPV), red blood cell distribution width (RDW) with DVT (11,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the relationship between NLR and aortic disease has been investigated by several studies [11,12]. Authors focus on the NLR level in aortic aneurysm and aortic dissection patients, and the predictive value of high NLR in mortality and other clinical outcomes [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, red cell distribution width (RDW) and RPR also played a critical role in inflammation and immune responses. Sbarouni et al [ 6 ] reported that RDW and RPR were significantly higher in patients with AAAD compared to aortic aneurysms and normal subjects, but not associated with mortality. In this study, the RDW levels changed slightly among the four patients until they died or were discharged, and the RPR levels were comparable among the four patients on admission.…”
mentioning
confidence: 99%